No Differential Effects of Neural and Psychological Explanations of Psychopathy on Moral Behavior - Blakey, Robert; Askelund, Adrian Dahl; Boccanera, Matilde; Immonen, Johanna; Plohl, Nejc; Popham, Cassandra; Sorger, Clarissa; Stuhlreyer, Julia (Frontiers in Psychology, 2018)
Research in neurocriminology has explored the link between neural functions and structures and the psychopathic disposition. This online experiment aimed to assess the effect of communicating the neuroscience of psychopathy on the degree to which lay people exhibited attitudes characteristic of psychopathy in particular in terms of moral behaviour. If psychopathy is blamed on the brain, people may feel less morally responsible for their own psychopathic tendencies. In the study, participants read false feedback about their own psychopathic traits supposedly inferred from their Facebook likes, described either in neurobiological or cognitive terms. Participants were randomly allocated to read that they either had above-average or below-average psychopathic traits. We found no support for the hypothesis that the neuroscientific explanation of psychopathy influences moral behaviour. This casts doubt on the fear that communicating the neuroscience of psychopathy will promote psychopathic attitudes.